Morphometric, meristic and growth patterns of Hemirhamphodon pogonognathus Bleeker (1865) from the waters around the University of Riau - Ari Fadli; Windarti Windarti; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Hemirhamphodon pogonognathus is a typeof freshwater fish that inhabit waters around the Riau University. This fish is potential for decorative fish. Information on biological, including morphometric, meristic, and growth patterns, however, is rare. To understand the morphometrical and meristicalcharacteristics and also the growth pattern of the fish, a research has been conducted February-March 2018. There were 100 fishes (33.35-82.65 TL mm and 1.3-0.1 gr BW). There were 28 morphological characteristic measured and 11 meristical characteristic counted. The meristicalcharacteristics obtained were as follows: D.15-17; P.5-8; V.5-6; A.8-9; C.17-20. The number of scale in the pre-dorsal fin was 47-52, around the body 52-62, in the caudal peduncle was 14-16, in the lateral line was 98-110, above lateral line was 19-25 and under lateral line was 25-31.Resylts  of Withney test shown that there were 9  morphometrical characteristic differences between male and female. They were height  of caudal-peducle depth, distance between dorsal fin and the base caudal fin, height of dorsal fin, length pectoral fin base, anal fin height, length of ventral fin base, height of ventral fin, length of caudal fin base, and height of caudal fin.The length-weight relationship shown that the growth of male and female was isometric. Keywords: freshwater fish, isometric, decorative fish, morphological characteristic, meristic characteristic